Does favorable mean fair? An empirical analysis of the fairness of HRM decisions - Lazauskaitė-Zabielskė, Jurgita (Psichologija, 2017)
Several decades of organizational justice research consistently show that employees accept the decisions made by organizations and authorities and are satisfied with them when they perceive those decisions to be fair (Colquitt et al., 2012). It is usually agreed that perceived fairness of decision outcomes (or distributive justice), decision making procedures (or procedural justice), and the behavior of decision makers (or interactional justice) depend on their correspondence with certain justice principles or rules (Cropanzano et al., 2001). However, even strict adherence to justice rules does not always help to attain fairness, and different goals of various HRM decisions require the application of different justice rules (Cropanzano & Ambrose, 2015). Moreover, some studies show that the fairness of employee judgments are based on those justice rules that allow to attain favorable results (Brockner & Wiesenfeld, 2005). However, such a selective application of justice rules is more intuitive than based on careful investigation. A systematic investigation is needed to determine the relative importance or weight of justice rules in various HRM decisions and how it depends on decision favorability. Therefore, the study was conducted with the aim to analyze the role of decision favorability and justice rules in determining perceived fairness across HRM decisions of performance appraisal, pay, benefits and opportunity to develop.440 employees were surveyed. Thirty percent of the respondents were male, seventy percent were female. The average age of respondents was 39.75 years, with 6.06 years of tenure in the organization. 25.5 percent of study participants were middle-level managers and 74.5 percent were subordinates.The results of the study reveal that decision favorability predicts the perceived justice of HRM decision outcomes, decision-making procedures and decision makers above and beyond fairness rules. When a favorable decision is made, the decision-making procedures, interpersonal treatment and the decisions themselves are perceived to be fairer. This result applies to all decisions investigated. Moreover, decision favorability also determines the weight of justice rules in predicting distributive, procedural and interactional justice of HRM decisions. An unfavorable performance appraisal decision is perceived to be fairer when it is equal for all employees, but not when it is favorable. Furthermore, an unfavorable pay decision is perceived to be fairer when it is equal and less equitable, while pay raise is perceived as fairer when it is equitable and not equal to other employees; also, when the decision maker provides all information and behaves properly. In addition, when an employee is awarded with benefits, fairness of procedures is based on their accuracy. Finally, when an employee is deprived of the opportunity to develop, decision making procedures are evaluated as fairer when they are accurate and the decision maker provides explanation. On the contrary, when an employee is awarded with an opportunity to develop, the accuracy of procedures and the explanation of a decision become less important for fairness judgements.
Keywords: decision favourability; distributive; procedural; and interactional justice; human resource management decision